After Industrial Citizenship: Market Citizenship or Citizenship at Work? - Fudge, Judy (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2005)
This article sketches the rise and fall of industrial citizenship in Canada, and presents two very different models of citizenship that might replace it. It begins by defining the concept of citizenship, and explaining how industrial citizenship has conventionally been understood. It then traces the genealogy of industrial citizenship in Canadian labour law, and how the processes of feminization, deregulation, and globalization have challenged it as a normative ideal and undermined the conditions that have sustained it. The article concludes by considering two scenarios for industrial citizenship in the future: one in which the substance of citizenship is circumscribed by an emphasis on the market, and the other in which citizenship is extended beyond employment to work.